2021
DOI: 10.1007/s11248-021-00256-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of agro-infiltration on N. benthamiana accessions

Abstract: Over the recent years, Nicotiana benthamiana has gained great importance as a chassis for the production of high value, low volume pharmaceuticals and/or active pharmaceutical ingredients (APIs). The process involving infiltration of the N. benthamiana leaves with Agrobacterium spp, harbouring vectors with the gene of interest, facilitates transient expression. To date, little information is available on the effect of the agro-infiltration process on the metabolome of N. benthamiana, which is necessary to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…All metabolites detected in the present study, except for unidentified molecular features, have been previously reported for individual Nicotiana species, mainly N. tabacum (Jassbi et al, 2017;Kaminski et al, 2020a). As previously reported for several N. benthamiana accessions, the present metabolite profiling did not detect any catechins or related/derived metabolites (Drapal et al, 2021b). This supports the hypothesis that the genus Nicotiana does not contain tannin synthesis, one of the major branches of the phenylpropanoid-derived biosynthesis (Vogt, 2010).…”
Section: Establishing the Chemotype Core Collection Of Genus Nicotianasupporting
confidence: 91%
See 1 more Smart Citation
“…All metabolites detected in the present study, except for unidentified molecular features, have been previously reported for individual Nicotiana species, mainly N. tabacum (Jassbi et al, 2017;Kaminski et al, 2020a). As previously reported for several N. benthamiana accessions, the present metabolite profiling did not detect any catechins or related/derived metabolites (Drapal et al, 2021b). This supports the hypothesis that the genus Nicotiana does not contain tannin synthesis, one of the major branches of the phenylpropanoid-derived biosynthesis (Vogt, 2010).…”
Section: Establishing the Chemotype Core Collection Of Genus Nicotianasupporting
confidence: 91%
“…The extracts for three different analytical platforms were extracted with one methanol/water/chloroform separation method as previously described (Drapal et al., 2020b). The polar phase was aliquoted for metabolite profiling (100 μl) by UPLC‐ESI‐QToF 6560 (Agilent Technologies, Stockport, UK) and for metabolite profiling (150 μl) by GC‐MS detection (GC‐MSD) in splitless mode (Agilent Technologies) as previously described (Drapal et al., 2021b; Price et al., 2016). The extracts were spiked with internal standards genistein (1 μg) and d4‐succinic acid (10 μg).…”
Section: Methodsmentioning
confidence: 99%
“…The QLD wild accession exhibits many morphological, developmental and metabolic differences to LAB 7,[14][15][16] , such as outcrossing flowers 7,14-16 , moth-attracting volatile production at night, and the robust capacity to produce anthocyanins (Figures 1C-D, S1, S2, Table S1). The levels of a range of metabolites such as phenolic acids, flavonoids, amino acid derivatives, and metabolites involved in defense responses [17][18][19][20] , such as nornicotine and hydroxygeranyl-linalool diterpene glycosides (HGL-DTG), exhibit marked differences between LAB and QLD (Figures 1E-F, S3, Table S2).…”
Section: An Additional N Benthamiana Ecotype Resourcementioning
confidence: 99%
“…All of this work has relied on plants derived from one accession line (that we term LAB), that appears to have originated from a single collection near the Granites gold mine in central Australia 7,14,15 (Figure 1B). Several additional ecotypes have recently been described 7,1416 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation